GAYA HIDUP DAN KEKAMBUHAN PADA PASIEN HIPERTENSI DI UPT PUSKESMAS JATINANGOR - Tuti Suprapti; Adzka Rijal; Siti Jundiah (NHM PRESS, 2021)
Hypertension is one of the cardiovascular diseases that need to be watched out for because this disease often occurs without clear symptoms until complications occur (the silent disease). Hypertensive disease that is not handled optimally will result in a return of symptoms, or is called a recurrence of hypertension. An unfavorable lifestyle is a factor in the recurrence of hypertension in addition to regular treatment and control. This study aims to determine the relationship between lifestyle and recurrence of hypertension in patients at UPT Puskesmas Jatinangor, Sumedang Regency. This research is a descriptive correlative research type with a cross sectional approach. The study population was all patients who went to UPT Puskesmas Jatinangor Sumedang. A sample of 63 patients with hypertension using purposive sampling technique. Collecting data using a lifestyle questionnaire totaling 24 items, and using a checklist for recurrence of hypertension in the last 1 month. The analysis used is univariate and bivariate with Chi-Square correlation test. The results of the Chi-Square correlation test show that there is a relationship between lifestyle and recurrence of hypertension in patients at UPT Puskesmas Jatinangor Sumedang with a significance value (p-value) = 0.000. Based on the results of this study, it is hoped that the Jatinangor Health Center can make a program to reduce the recurrence of hypertension caused by an unhealthy lifestyle, including counseling and joint exercise for hypertensive patients.